Accessing multiple polyethylene grades via a single redox-active olefin polymerization catalyst. Issue 7 (12th April 2017) - Anderson, W. Curtis; Park, Sang H.; Brown, Lauren A.; Kaiser, Jordan M.; Long, Brian K.
Abstract : Access to more than one polyethylene grade is realized via utilization of a Ni-based olefin polymerization catalyst bearing a redox-active α-diimine ligand. Abstract : The ability to control catalytic activity via redox-activity has had a significant impact on the field of polymerization catalysis. Herein, we describe the synthesis of three unique Ni-based olefin polymerization catalysts bearing redox-active α-diimine ligands. We will demonstrate that catalysts bearing butanedione- or glyoxal-derived ligands display little to no differentiation as a function of redox-state. However, in stark contrast we will show that the catalyst bearing an acenaphthenequinone-derived ligand is capable of producing either medium-density or very-low-density polyethylene based purely on its ligand-based redox-state. This ability to access more than one polyethylene grade via a single redox-active catalyst is unprecedented.